2010
DOI: 10.1371/journal.pone.0009712
|View full text |Cite
|
Sign up to set email alerts
|

Human Breast Cancer Cell Lines Co-Express Neuronal, Epithelial, and Melanocytic Differentiation Markers In Vitro and In Vivo

Abstract: Differentiation programs are aberrant in cancer cells allowing them to express differentiation markers in addition to their tissue of origin. In the present study, we demonstrate the multi-lineage differentiation potential of breast cancer cell lines to express multiple neuronal/glial lineage-specific markers as well as mammary epithelial and melanocytic-specific markers. Multilineage expression was detected in luminal (MCF-7 and SKBR3) and basal (MDA-MB-231) types of human breast cancer cell lines. We also ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
45
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 13 publications
3
45
0
1
Order By: Relevance
“…This observation indicates that the tumor vasculature of MDA-MB-435, as seen in real time at multiple time points in individual mice, was highly permeable and leaky. This is consistent with previous reports (2,(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 94%
“…This observation indicates that the tumor vasculature of MDA-MB-435, as seen in real time at multiple time points in individual mice, was highly permeable and leaky. This is consistent with previous reports (2,(18)(19)(20)(21)(22).…”
Section: Resultssupporting
confidence: 94%
“…We are showing the evidence of expression of both SV2 protein and mRNA in non-tumor and transformed breast cell lines; we found SV2 A, B and C isoforms expression in breast cell lines. A recent research indicates that cells of the luminal epithelium of ducts and lobules of human mammary glands express neuroendocrine markers such as vesicular monoamine transporter 2 and chromogranin B, as well as the regulatory peptides obestatin, ghrelin, adrenomedullin and apelin (Gronberg et al, 2010), furthermore neuronal/glial markers (nestin, TUBB3 and GFAP) have been identified in MCF-10A, SKBR3 and MBA-MB-231 cell lines, although they are overexpressed in tumor-cell lines, these breast cancer lines are showing a multi-lineage differentiation potential of breast cancer cell lines to express multiple neuronal/glial lineage-specific markers as well as mammary epithelial and melanocyticspecific markers (Zhang et al, 2010). Furthermore, in the same study ectoderm multi-lineage transdifferentiation was also found in human melanoma (Ul-MeL) and glioblastoma cell lines (U87 and D54).…”
Section: Discussionmentioning
confidence: 99%
“…The role of SV2 in breast cells could be associated to secretory nature of mammary glands, and may interact with other vesicle proteins such as synaptobrevin, which is essential for secretion but not for the development of synaptic process (Ahnert-Hilger et al, 1996), however, the SV2 role in cancer is not clear, although it is already reported in others types of cancer, for instance, brain (de Groot et al, 2010;, pancreas (Jakobsen et al, 2002), gastrointestinal tract (Jakobsen et al, 2002;Bumming et al, 2007 ), liver (Hanoun et al, 2010), bladder (Coelho et al, 2010), prostate (Karsenty et al, 2009) and adrenals (Li et al, 1999) tumors among others, where SV2 has already been proposed as molecular and transdifferentiation marker of neural nature (Nilsson et al, 2004;Zhang et al, 2010). This is possible because in the cancerous state the terminal differentiation to the anticipated cellular type is altered and the phenomena of lineage infidelity that is associated with the ability of cancer cells to transdifferentiate, occurs in different cancer types and occur in breast cancer (Zhang et al, 2010); thus, it is a commune phenomenon that cancer cell turns-off/-on non-habitual genes changing the ontogeny to evade the immune system and hold the linage independence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…De plus, la première étape ressemble à une dédifférenciation : la reprogrammation directe ne passe donc pas par une identité mixte. Ceci peut représenter un mécanisme de protection de l'organisme puisque l'expression simultanée de plusieurs types cellulaires a été observée dans divers cancers [11]. Enfin, la redifférenciation par étapes en un neurone PDA semble mimer le processus de diffé-renciation neuronale embryonnaire.…”
Section: Dernière Heure Magazineunclassified